Labour in global value chains: the case of South African fish exporting companies - Mufukari, Panashe (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
Global value chains have reconfigured the organization of production and distribution across the world. Such a transformation has led to production fragmentation across multiple locations and the specialization of firms some of which now produce only one component of a larger product. Transformation in international trade has enabled multinational corporations to outsource production and operations to low-cost locations, which are mainly found in the Global South. Global value chains research explores these dynamics. This research began with Hopkins and Wallerstein's work on world-systems analysis, which was concerned with the likelihood that these chains are characterized by inequality. However, later approaches, focused on Global Commodity Chains (GCCs), Global Value Chains (GVCs) and Global Production Networks (GPNs), suggested that participation in global value chains could advance development for Global South nations and result in "social upgrading" and decent work for those employed by companies that participate in these chains. This thesis explores the lived experiences of workers in South African fish exporting companies in the city of Gqeberha, to assess whether participation in global value chains does indeed mean workers experience decent working conditions. The findings of the research suggest that global value chains research needs to pay increased attention to workers. The study also emphasizes the importance of migrant labour, both internal migrant labour and international migrant labour in global value chains. By giving attention to both internal and international migrant labour, the complexity of the workforce is highlighted. Accordingly, the study calls for a comprehensive approach to the labour issue in global chains because the diverse locations and contexts shape workers' experiences with and outcomes from participation in global chains. The study concludes that the world-systems tradition remains relevant for understanding the contemporary issues of unequal exchange, hierarchy of occupational tasks and wages, and exploitation within these global chains, a stance that diverges from mainstream scholarship in which world-systems tradition is deemed as having limited contemporary applicability.
Keywords: Global value chain; Migrant labor -- South Africa; Workforce casualisation; Casual labor -- South Africa; Precarious employment -- South Africa; Exploitation of labour